Insect Diversity and Intensity of Leaf Caterpillar (Plutella xylostella) Attacks on Nita F1 Variety Kailan Plants with the Application of Several Vegetable Pesticides - Fitriani, Laela; Siriyah, Siti Latifatus; Laksono, Rommy Andhika (Jurnal Biologi Tropis, 2025)
Pest attacks are an important problem in vegetable cultivation practices. Pest control using synthetic pesticides is still widely used, but excessive use has a negative impact on human health and the environment, one of which is insect diversity. As an alternative to pest control, pesticides can be used with active ingredients that are secondary metabolites from plants or commonly called plant pesticides. The purpose of this study is to evaluate the influence of vegetable pesticides on insect diversity and the intensity of leaf caterpillar pest attacks on kailan plants. The method used is an experimental method using a single-factor Random Group Design (RAK) consisting of 5 treatments and 5 replicates. These treatments include K (Control), PP (Papaya Leaf Pesticide), PM (Neem Leaf Pesticide), PB (Babanandan Leaf Pesticide), and PS (Synthetic Pesticide). Insect sampling was done 4 times at 7-28 hst with an interval of 7 days using slope pifall traps, yellow board traps and insect nets. The data was analyzed using ANOVA variety analysis and a follow-up test of BNT at 5%.  The results of the variance analysis showed that the PP treatment was able to maintain diversity with an index value of H'= 2.689 and an abundance of 369.800. PP treatment gave the lowest caterpillar attack intensity value ranging from 0.833% – 15,000%, which is a plant-based pesticide treatment with results close to synthetic pesticide treatment. Therefore, papaya leaf plant pesticides can be recommended as an alternative pesticide to maintain diversity and suppress the intensity of pest attacks in kailan cultivation.